Engaging with C.H. Dodd on the gospel of John: sixty years of tradition and interpretation - Thatcher, Tom (Cambridge University Press, 2013)
C. H. Dodd's Historical Tradition in the Fourth Gospel, published in 1963, marked a milestone in New Testament research and has become a standard resource for the study of John. Historically biblical scholars have concentrated on the Synoptic Gospels: Matthew, Mark and Luke. However, Dodd's book encouraged scholars to take John seriously as a source for the life of Jesus. This volume both reflects upon and looks beyond Dodd's writings to address the implications, limitations and potential of his groundbreaking research and its programmatic approach to charting a course for future research on the Gospel of John. Leading biblical scholars demonstrate the recent surge of interest in John's distinctive witness to Jesus, and also in Dodd's work as the harbinger of advancements in the study of the Fourth Gospel. This volume will be invaluable to all those studying the New Testament, Johannine theology and the history of the early Church.